2019
DOI: 10.1021/acs.est.9b04064
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Scale Investigations Reveal Noncovalent Bonding Underlying the Adsorption of Environmental DNA on Mica

Abstract: Mineral–soil organic matter (SOM including DNA, proteins, and polysaccharides) associations formed through various interactions, play a key role in regulating long-term SOM preservation. The mechanisms underlying DNA–mineral and DNA–protein/polysaccharide interactions at nanometer and molecular scales in environmentally relevant solutions remain uncertain. Here, we present a model mineral–SOM system consisting of mineral (mica)–nucleic acid (environmental DNA, eDNA)/protein (bovine serum albumin)/polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
3
34
0
Order By: Relevance
“…The change in the height of the tip as it moves across the surface is related to the surface morphology. Zhai et al [77] studied DNA adsorption on mica mineral surfaces by attaching a DNA fragment to an AFM tip. They concluded that the DNA adsorbs on the surface as an outer-sphere complex.…”
Section: Outer-sphere Adsorptionmentioning
confidence: 99%
“…The change in the height of the tip as it moves across the surface is related to the surface morphology. Zhai et al [77] studied DNA adsorption on mica mineral surfaces by attaching a DNA fragment to an AFM tip. They concluded that the DNA adsorbs on the surface as an outer-sphere complex.…”
Section: Outer-sphere Adsorptionmentioning
confidence: 99%
“…Some phyllosilicates showed a remarkable capability of catalysis of biomolecules and condensation, organization of biopolymers and even cells (Heinz, 2012; Tavanaee et al ., 2017; Pietrement et al ., 2018). Within this kind of studies, scanning probe microscopy (SPM) methods provide unique information and a clear picture at the micro and nanoscale of the system under consideration showing features related to the adsorption process and conformation of the objects onto the surface (Moro et al ., 2015; Math et al ., 2019; Zhai et al ., 2019), even in the case of particular, complex‐to‐treat and tricky specimens, such as single biomolecule behaviour. However, when dealing with small objects (molecules or small biopolymers), and when imaging information at the subnanometre level is recorded, to strengthen the interpretation of the results, it is necessary to couple the imaging methods with atomic‐scale simulations, either of molecular dynamics or quantum‐mechanics type.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to accumulation in certain parts of the water column, or changing speed of diffusion (Cai et al 2006a;Cai et al 2006b). When bound particles are too dense, it can also promote deposition and accumulation of eDNA in the substrate (Zhai et al 2019). Size of suspended particles also influences this dynamic, as finer substrates tend to capture more eDNA due to smaller pores (Shogren et al 2016).…”
Section: Discussionmentioning
confidence: 99%